Decreased colorectal cancer incidence and mortality in a diverse urban population with increased colonoscopy screening - Jennifer J. Brown; Charles K. Asumeng; David Greenwald; Matthew Weissman; Ann Zauber; Jared Striplin; Olivia Weng; Justin M. List; Shannon M. Farley; Sidney J. Winawer (BMC, 2021)
Abstract Background Although colorectal cancer screening has contributed to decreased incidence and mortality, disparities are present by race/ethnicity. The Citywide Colon Cancer Control Coalition (C5) and NYC Department of Health and Mental Hygiene (DOHMH) promoted screening colonoscopy from 2003 on, and hypothesized future reductions in CRC incidence, mortality and racial/ethnic disparities. Methods We assessed annual percent change (APC) in NYC CRC incidence, stage and mortality rates through 2016 in a longitudinal cross-sectional study of NY State Cancer Registry, NYC Vital Statistics, and NYC Community Health Survey (CHS) data. Linear regression tested associations between CRC mortality rates and risk factors. Results Overall CRC incidence rates from 2000 decreased 2.8% yearly from 54.1 to 37.3/100,000 population in 2016, and mortality rates from 2003 decreased 2.9% yearly from 21.0 to 13.9 in 2016 at similar rates for all racial/ethnic groups. Local stage disease decreased overall with a transient increase from 2002 to 2007. In 2016, CRC incidence was higher among Blacks (42.5 per 100,000) than Whites (38.0), Latinos (31.7) and Asians (30.0). In 2016, Blacks had higher mortality rates (17.9), than Whites (15.2), Latinos (10.4) and Asians (8.8). In 2016, colonoscopy rates among Blacks were 72.2%, Latinos 71.1%, Whites 67.2%, and Asians, 60.9%. CRC mortality rates varied by neighborhood and were independently associated with Black race, CRC risk factors and access to care. Conclusions In a diverse urban population, a citywide campaign to increase screening colonoscopy was associated with decreased incidence and mortality among all ethnic/racial groups. Higher CRC burden among the Black population demonstrate more interventions are needed to improve equity.